Visual Studio tools for Office 2007 : VSTO for Excel, Word, and Outlook - Carter, Eric (Microsoft .NET development series., 2009)
Visual Studio Tools for Office 2007: VSTO for Excel, Word, and Outlook is the definitive book on VSTO 2008 programming, written by the inventors of the technology. VSTO is a set of tools that allows professional developers to use the full power of Microsoft Visual Studio 2008 and the .NET Framework to program against Microsoft Office 2007. This book delivers in one place all the information you need to succeed using VSTO to program against Word 2007, Excel 2007, and Outlook 2007, and provides the necessary background to customize Visio 2007, Publisher 2007, and PowerPoint 2007. It introduces the Office 2007 object models, covers the most commonly used objects in those object models, and will help you avoid the pitfalls caused by the COM origins of the Office object models. Developers who wish to program against Office 2003 should consult Carter and Lippert's previous book, Visual Studio Tools for Office. In VSTO 2008, you can build add-ins for all the major Office 2007 applications, build application-level custom task panes, customize the new Office Ribbon, modify Outlook's user interface using Form Regions, and easily deploy everything you build using ClickOnce. Carter and Lippert cover their subject matter with deft insight into the needs of .NET developers learning VSTO, based on the deep knowledge that comes from the authors' unique perspective of living and breathing VSTO for the past six years. This book Explains the architecture of Microsoft Office programming and introduces the object models Covers the main ways Office applications are customized and extended Explores the ways of customizing Excel, Word, and Outlook, and plumbs the depths of programming with their events and object models Introduces the VSTO programming model Teaches how to use Windows Forms and WPF in VSTO and how to work with the Document Actions Pane and application-level task panes Delves into VSTO data programming and server data scenarios Teaches ClickOnce VSTO deployment This is the one book you need to succeed in programming against Office 2007. C# and Visual Basic .NET Code samples for download can be found here: http://www.informit.com/store/product.aspx?isbn=0321533216.